PEMBENTUKAN KARAKTER BERBASIS KEGIATAN KELOMPOK AGAMA PESERTA DIDIK DI SEKOLAH - lutfi, Attabik; abbas, aries; arifin, muhammad; fathurrahman, fajar (Pascasarjana Universitas Islam Jakarta, 2022)
Abstract. Education is currently less effective in providing Emotional Quotient education. The curriculum only gives a little content of character education, realizing the importance of character, to increase the intensity and quality of the implementation of character education in formal educational institutions. Therefore, formal educational institutions as an official forum for fostering the younger generation are expected to increase their role in shaping the personality of students through increasing the intensity and quality of character education. Islamic Religious Education, which is considered to need a solution due to the limited time allocation available in the schedule of teaching and learning religion for students. So we need a strategy that is applicable and meets the elements of SMART planning (Specific, Measurable, Achievable, Realistic, and Timely). The results of this study are the Implementation of the PAI Based Character Building Strategy through Activities followed by the students. PAI Based Character Building Strategy Model Spiritual Activity Assistance (Project Based Learning), namely: a) Knowing about zakat, b) Feeling the obligation of zakat, c) Performing governance/ distribute zakat.